Identification of renal podocytes in multiple species: higher vertebrates are vimentin positive/lower vertebrates are desmin positive - Yaoita, Eishin; Franke, Werner (Histochemistry and cell biology, 1999)
We sought to characterize podocytes in the kidneys of numerous species from amphibians to mammals because of the pivotal function of these cells in renal diseases. For this purpose, intermediate filament (IF) proteins of podocytes were examined by immunofluorescence microscopy using antibodies against vimentin, cytokeratins, and desmin. These staining patterns were then compared to those of parietal cells of Bowman’s capsule and tubular cells of the first portion of the proximal tubule from the same sources. As a result, podocytes from mammals (rat, rabbit, dog, cow, and human) and birds (chicken) showed intense vimentin staining without exception, but rarely staining for cytokeratins or desmin. Parietal cells from all these animals were highly heterogeneous with respect to cytokeratin or vimentin staining. Of the tubular cells, only those from humans and chickens were reactive and then only with anti-cytokeratin antibodies. In the reptiles (Chrysemys scripta elegans, Chinemys reeveri, Elaphe quadrivirgata, and Anolis carolinensis), podocytes and other epithelial cells were positive for cytokeratins. Vimentin staining differed among the species, but was not characteristic for podocytes. Anti-desmin antibody reacted strongly only with podocytes from Anolis. In amphibians (Rana catesbeiana and Xenopus laevis), anti-desmin antibody stained podocytes more intensely than any other cell. Cytokeratin and vimentin staining did not differentiate podocytes from the other cell types. These findings indicate that podocytes are characterized by intense vimentin staining in the higher vertebrates and by desmin staining in the lower vertebrates denoting potentially distinctive physiological functions of IF proteins in podocytes from each of these groups.